PEMBERIAN FUNGI MIKORIZA ARBUSKULA DAN BIOCHAR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max (L.) Merril) PADA TANAH ULTISOL - Sidik Yunedi; Andrian Perdana (Jurnal Agroteknologi, 2023)
Soybean is one of the main needs and sources of vegetable protein for Indonesian. National needs of soybean continue to increase in line with the increase of population, but soybean production has not been able to meet national needs. Therefore, efforts need to be made to increase soybean production by utilizing marginal land with using arbuscular mycorrhizal fungi and biochar. The aim of this study was to determine the effect of single factors of arbuscular mycorrhizal fungi (AMF), biochar and interaction of these two factors on the growth and yield of soybean in Ultisol soil. This research was conducted from December until March 2019. The research used 3 x 3 factorial completely randomized design with three replications. The first factor was AMF dosage consist of 3 levels : M0 (0 g per plant), M1 (15 g per plant), M2 (30 g per plant) and the second factor was type of biochar consist of 3 levels : B0 (without biochar), B1 (biochar of rice husk), B2 (biochar of coconut shell). The observation data that obtained were analyzed statistically using analysis of variance (ANOVA). The results of variance analysis were continued by Duncan's multiple range test at level 5%. The results showed that the treatment of AMF improved all growth and yield parameters and the single biochar can not improve all growth and yield parameters. The interaction between AMF and biochar did not improve all parameters of growth and yield of soybean.